Environmental Awareness of Secondary and Senior Secondary Students: Promoting Environmental Awareness among Secondary and Senior Secondary Students in Rural Areas (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study gathereddata through survey method. Survey of 600 secondary and senior secondary school  students in the city centre and villages of Kurukshetradistrict found  that rural students andstudents studying in government schools were still not aware of the variousthreats of environment and natural calamities and most  of the  Government  rural schools  did  not possess  basic  literature related  to Environment (inregional language). The paper suggested environmental awareness campaigns likecompetitions, vanmahotsavs, tree plantation, celebration of world environmentalday etc. be carried out  in these areas.